Rules of song development and their use in vocal interactions by birds with large repertoires - Geberzahn,Nicole (2004)
Songbirds are well known for settling their disputes by vocal signals, and their singing plays a dominant role. Most studies on this issue have concentrated on bird species that develop and use small vocal repertoires. In this article we will go farther and focus on examples of how species with large song repertoires make use of their vocal competence. In particular, we will outline the study of interaction rules which have been elucidated by examining time- and pattern-specific relationships between signals exchanged by territorial neighbors. First we present an inquiry into the rules of song learning and development. In birds with large song repertoires, the ontogeny of such rules proceeds along a number of trajectories which help in understanding the often remarkable accomplishments of adult birds. In both approaches, our model species will be the Common Nightingale Luscinia megarhynchos that has been investigated intensively in the field and in the laboratory.